SAT0235 Assessment of Achilles Enthesitis in the Spondyloarthritis by Colour Doppler Ultrasound. (9th June 2015) - Rekik, S.; Jrad, M.; Aouadi, A.; Boussaid, S.; Ajleni, H.; Sahli, H.; Cheour, E.; Mizouni, H.; Elleuch, M.
Abstract : Background: Enthesitis is the inflammatory process marked by the insertions of tendons, ligaments and joint capsules on the bone and it is the cardinal feature and diagnostic criteria of spondyloarthritis (SpA). Although, it is usually revealed by clinical examination, the enthesitis can be asymptomatic, both in the axial and peripheral skeleta. Objectives: Our objective is to investigate by colour Doppler ultrasound (CDU) the modality and the frequency of involvement of Achilles enthesitis, the main site of involvement in SpA after calcaneal entheses, to identify its characteristic features, and to correlate these findings with clinical complaints and radiographic evidence. Methods: Our study is prospective. Thirty patients with SpA diagnosis were included. The diagnoses were ankylosing spondylitis in 18 patients, psoriatic arthritis in 8, SpA associated with inflammatory bowel diseases (IBD) in 3, and Reiter's disease in one patient. All of them were clinically evaluated and underwent CDU examination of Achilles entheses. Particular attention was given to the detection of enthesis thickness, structure, cortical bone insertion, junction between tendon and entheses, body of tendon, calcifications, erosions, bursae, power Doppler signal and vascularization. Results: Patients male/female ratio was 4 (24/6), mean age was 30 (range 16-53) years and mean disease duration was 8 (range 1-13)years. Mean (SD) BASDAI and BASFI scores were 33 and 64 respectively. Twenty-three of the 30 SpA patients (76%) showed at least one abnormal finding of the enthesitis on CDU examination, affecting 43 of 60 Achilles entheses examined (71%). Only 11 Achilles entheses (18%) showed vascular signals in the periosteal areas or in the area of enthesis fibrocartilage. Ultimate correlations were found between pain and tenderness with increased vascularity. In addition, 29 (48%) and 8 (14%) of 60 Achilles entheses examined showed, respectively, cortical bone irregularities and erosions. Fourteen (87%) of 16 clinically detected Achilles enthesitis and 4 (57%) of 7 Achilles entheses with swelling on clinical examination presented corresponding abnormalities on CDU examination. CDU revealed Achilles tendon calcifications in 30% without significant correlation between talalgia or sex of patients but with excellent agreement with radiography. Deep retrocalcaneal bursitis was found in 3 (13%) and there was a significantly correlation with talalgia. Conclusions: This study demonstrates the characteristic features of Achilles enthesitis detectable by CDU in the SpA and shows a good correlation with clinical as well as with radiography findings. It may be useful and complementary to the clinical evaluation to track down this reach of Achilles tendon. Further researches are needed to improve the role of CDU in diagnosis and follow up of SpA course. References: Li CA, Kim HO, Lee SY, Lee SI. Assessment of Achilles enthesitis in the spondyloarthropathies by colour Doppler energy ultrasound in the context of the "enthesis organ". Scand J Rheumatol. 2010 Mar;39(2):141-7. Disclosure of Interest: None declared